Regenerative medicine: Clinical applications and future perspectives. Issue 1 (March 2017) - Colombo, Federica; Sampogna, Gianluca; Cocozza, Giovanni; Guraya, Salman Yousuf; Forgione, Antonello
Abstract: After many years of basic research, regenerative medicine (RM) is now beginning to represent a valuable tool to cure several clinical conditions in both acute injuries and chronic diseases. The aim of this study is to update readers on current clinical applications of some selected organs and pathologies which may benefit from RM. An extensive literature research was performed using PubMed, Google and specialized journals. RM has achieved great successes, but there are still several challenges to tackle before it could be used on a daily basis in clinical practice. The crucial point of this revolution is represented by the appropriate and valid translation from bench to bedside.